1987
DOI: 10.1021/bi00382a045
|View full text |Cite
|
Sign up to set email alerts
|

Stratum corneum lipid phase transitions and water barrier properties

Abstract: In mammals, the outer skin layer, the stratum corneum, is the ultimate barrier to water loss. In order to relate barrier function to stratum corneum structure, samples from porcine skin were investigated by using differential scanning calorimetry (DSC), infrared (IR) spectroscopy, and water permeability techniques. Results of DSC and IR studies show that stratum corneum lipids undergo thermal transitions between 60 and 80 degrees C similar to lipid thermotropic transitions seen in a variety of synthetic and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
86
0
4

Year Published

1990
1990
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(97 citation statements)
references
References 33 publications
7
86
0
4
Order By: Relevance
“…Normally, hydrocarbons within the lipid domain of the SC below their transition temperature exist in a trans conformation. When the lipid domain becomes fluidized by thermal induction (46) and/or by treatment with chemical enhancer(s), an increase in the wavenumber of CH2 frequency would occur due to increased motional freedom and numbers of gauche conformers of lipid alkyl chains (47). Therefore, this increased lipid fluidity after combination treatment with terpenes and PG might be responsible for the enhanced permeability of LOM through hairless mouse skin.…”
Section: Skin Permeation Studiesmentioning
confidence: 99%
“…Normally, hydrocarbons within the lipid domain of the SC below their transition temperature exist in a trans conformation. When the lipid domain becomes fluidized by thermal induction (46) and/or by treatment with chemical enhancer(s), an increase in the wavenumber of CH2 frequency would occur due to increased motional freedom and numbers of gauche conformers of lipid alkyl chains (47). Therefore, this increased lipid fluidity after combination treatment with terpenes and PG might be responsible for the enhanced permeability of LOM through hairless mouse skin.…”
Section: Skin Permeation Studiesmentioning
confidence: 99%
“…Therefore, the objective of this paper was to investigate molecular changes in stratum corneum after treatment with different formulations of laurocapram, N-0915, DMBIS, DMMCBI and TBDOC using the two analytical methods of DSC and ATR-FTIR that provide independent yet complementary information regarding the interaction of enhancer/retardants within the SC (12,13). Though there are reports of DEET affecting SC when used as enhancer to increase the permeation of drugs (14), in our previous study (3), DEET was merely used as a model permeant to evaluate the permeation effects of penetration modifier formulations.…”
Section: Introductionmentioning
confidence: 99%
“…In the SC of mammals, ceramides account for as much as 50% of the total lipids (Raith and Neubert, 2000). From work mostly on mammals, but also a few domestic species of birds, evidence has accumulated that the SC forms the barrier to water vapor diffusion from the animal to the environment (Blank, 1953;Blank et al, 1984;Golden et al, 1987;Warner et al, 1988;Elias and Menon, 1991;Peltonen et al, 2000). Haugen et al (2003) have shown that free fatty acids, cholesterol and ceramides are the major constituents of SC in wild larks (skylarks, woodlarks, hoopoe larks and Dunn's larks) from mesic, semi-arid and arid environments.…”
mentioning
confidence: 99%